Trajectories of urban insertion of aymaras in Tacna: the construction of the New City district - Ponce Vargas, Berchman Alfonso (2018)
This research analyzes the trajectories of Aymara migrants in Tacna, especially during the creation of the new city district, with the aim of reflecting on the transformation of the sociocultural references of the city. Using qualitative methods such as semi-structured interviews and participant observation, an immersion took place in the new city neighborhoods during November 2016, January and February 2017. The results of the research show us the importance of the networks of reciprocal exchange between migrants Aymare of rural origin to be inserted in the city. In this sense, we conclude that the new City Foundation expresses the concentration and increase of internal cohesion in the group of migrants Aymara in Tacna and represents the transformation of the status of the Aymara migrant to Tacna resident.